Mapping Social and Economic Vulnerability in Forest and Peatland Fire Disaster in Bengkalis Regency, Riau Province - Riyanto, Eko Ahmad (Forum Geografi, 2015)
The aims of this research are (1) analyzing social and economic vulnerability of forest and peat land fire disaster in Bengkalis Regency; (2) Mapping social and economic vulnerability of forest and peat land fire disaster in Bengkalis Regency. Â Research Variable is social and economic vulnerability. The data that used is primary and secondary data with survey method. Analysis method is scoring and weightings. After that classified based on the value of the score to determine the level of vulnerability. The analysis based on the head of National Agency for Disaster Management (Perka BNPB) Number 02.2012 and literatures study. The results of research show that social vulnerability of forest and peat land fire in Bengkalis Regency is medium vulnerability because it has value of social vulnerability is 0.46663. While economic vulnerability in Bengkalis Regency is low vulnerability because economic vulnerability is 0.3333. In addition, required mitigation that is quick and appropriate by governments of Bengkalis Regency and the local community in management of forest and peat land fire disaster.